A linguistic picture of the world and expression of emotions through the prism of expressive lexis - SIROKA, DANKA (Journal of Education Culture and Society, 2020)
This paper deals with expressive lexis, which is understood as the expression of emotions. Through this prism we would like to present a picture of the world which is formed by the opposites, emotional – rational. This picture would also present some examples of speech that is created in the mind as a result of man’s preferences and values. The relation of language and mind, formation of a picture of the world on the basis of both linguistic and extralinguistic foundations, projection of emotions and assessments on language – all of these components are inspiring avenues and this paper trys to enlighten the basis of expressive linguistic inventory of the users of the Slovak language.